Evaluating teff grass as a summer forage - Davidson, Jeremy Matthew (Kansas State University, 2018)
Finding a high-value forage crop with limited water requirements to produce livestock feed is becoming increasingly important as producers adapt to restricted water supply conditions. Our objectives were to determine the forage yield, nutritive values, and crop water productivity (CWP) of teff grass (Eragrostis tef [Zucc.] Trotter) under field conditions when compared to sorghum sudangrass (SS, S. x drummondii[(Nees ex. Steud.) Millsp. & Chase]) and pearl millet (PM, P. glaucum [L.]R.Br.). Crop water productivity was determined by dividing above-ground biomass by crop water use. Crop water use was determined by the summation of soil water depletion, precipitation, and irrigation. Yield was determined by quadrat area clippings of above-ground biomass. Nutritive value was determined using wet chemical analysis. Cultivars showed significant differences in biomass production and CWP in both years. Excalibur teff grass variety had the greatest CWP (418 kg ha⁻¹ cm⁻¹) 40 days after planting (DAP) in 2016, and was similar to SS and PM for the rest of the season until 58 DAP. Pearl millet had the greatest overall CWP (443 kg ha⁻¹ cm⁻¹) at 44 DAP. In 2017, sorghum sudangrass had significantly greater CWP than teff grass and pearl millet throughout most of the season. Among the teff varieties, Haymore had the greatest CWP (239 kg ha⁻¹ cm⁻¹) when harvested 10 days after boot stage (DAB). Crude protein values of teff grass varieties ranged from 9.3% to 21.3%, depending on the harvest date and year. Teff grass showed equivalent or greater nitrogen use efficiency (27.8 – 88.8 kg biomass kg⁻¹ N applied) in our study than previously reported. Teff grass demonstrated potential to provide producers with a fast-growing and competitive forage crop with less overall water use due to a shortened growing season.
Keywords: Eragrostis tef; Forage quality; Crop water use; Nutritive valueTeff